Discipline with dignity [ new challenges, new solutions - Curwin, Richard L. , 1944-; Mendler, Allen N.; Mendler, Brian D.; Gale Group (Alexandria, Virginia : Association for Supervision and Curriculum Development, 2008)
Offers practical solutions that focus on relationship building, curriculum relevance, and academic success. Emphasizes the prevention of problems by helping students to understand each other, work well together, and develop responsibility for their own actions. Also includes intervention strategies for handling common and severe problems in dignified ways
1. Discipline -- 2. Dignity and responsibility in the classroom -- 3. The three key dimensions -- 4. The social contract -- 5. Consequences -- 6. Taking action -- 7. Managing stress effectively -- 8. Strategies for students who chronically misbehave -- 9. Teaching strategies and classroom setup -- 10. Special problems
Includes bibliographical references (p. 239-243) and index
Keywords: Problem children -- Education -- United States; School discipline -- United States